STRATEGIC PLANNING, ORGANIZATIONAL CULTURE, ANALYSIS OF ORGANIZATIONAL PERFORMANCE IN STRATEGIC CHANGE MANAGEMENT MEDIATION IN STATE INTELLIGENCE AGENCY - Nugraha, Dani; Daihani, Dadan Umar; Kusnadi (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this study is to realize the legal, administrative and physical order of State Property in the State Intelligence Agency towards effective, efficient, optimal, and accountable management of State Property, as well as transparency, strategies and important steps are needed to realize change. In supporting the policy-making process related to State Property, it is necessary to fulfill basic information in the form of current and actual goods data by carrying out updates through periodic inventory of State Property.The research design and method used in this research is hypothesis testing. This research is a quantitative non-experimental, using a questionnaire given to 98 respondents. This research was conducted at the Logistics Bureau of the State Intelligence Agency. Data analysis using SPSS and PLS.3.20 software with multivariate Structural Equation Model (SEM) analysis method.The results of this study indicate that: Strategic Planning and Organizational Culture on Strategic Change Management are positive and significant. The influence of Strategic Change Management on Organizational Performance is positive and significant. The influence of Strategic Change Management mediating Strategic Planning and Organizational Culture on Organizational Performance is positive and significant. It means that the higher/positive mediation of Strategic Change Management on Strategic Planning and Organizational Culture, the higher/positive Organizational Performance. The theoretical implication of Strategic Change Management as mediating to Strategic Planning and Organizational Culture able to improve Organizational Performance, by improving Strategic Change Management through increasing its dimensions will be able to improve the Organizational Performance of the State Intelligence Agency.